Exploring the effects of indoor temperature on college students' physiological responses, cognitive performance and a concentration index derived from EEG signals. (December 2022) - Li, Yanxue; Li, Shanshan; Gao, Weijun; Xu, Wenya; Xu, Yang; Wang, Jian
Abstract: This paper reports an experimental study on college students in a climate chamber, analyzed the scenes of measured skin temperature, EEG activity and task performance of subjects exposed to three temperatures. The concentration performances of the subject task were evaluated by measured neurophysiological parameters. Results shown that there were gender differences in local skin temperatures and EEG-based concentration index at the indoor temperatures to which they were exposed, females' mean skin temperature is more sensitive to temperature steps. Accuracy divided by response time was proposed as a performance index, the influence of exposed temperature on two indicators depends on the type of cognitive task. The concentration index was more affected by cold in the male subjects. Experimental results strongly confirmed that EEG-based concentration index should be affected by indoor temperatures. Furthermore, a correlational analysis identified the close relationship between concentration index and performance index. Highlights: Physiological responses of subjects to different indoor temperatures. Identify gender differences in skin temperature and concentration index. Analyze the task performances of subjects under various conditions. Concentration index was closely and linearly correlated with the performance index.